Kajian Penambahan Gambir sebagai Bahan Penyamak Nabati terhadap Mutu Kimiawi Kulit Kambing - I. Juliyarsi; D. Novia; J. Helson (Universitas Andalas, 2013)
Gambier contains tannin which functions as vegetable tanning material. This study aimed to determine, the gambier addition to produces the best chemical quality leather according to Indonesian National Standard chemical quality goatleather (SNI 06-0463-1989). The method was used experimental method randomized block design, which consists of 5 treatments with 4 replications. Treatment of this study was added the gambier percentage (%), each treatment consisting of: treatment A: 15%, B: 20%, C: 25%, D: 30%, and E: 35%. The variables were measured water content, oil/fat content, water-soluble substances content, levels of substances rawhide, levels of insoluble ash in the water, levels of tanning substances (tannins) bound and the tanning degree. The results showed a significantly different effect (P <0.05) to decrease water content, levels of substances rawhide, levels of substances soluble in water and increasing tanning degree and did not differ significantly (P> 0.05) oil/fat content, ash content and levels of tanning substances (tannins) bound. The conclusion of this study was the addition of 25% was the best gambier percentage, with 17.06±0.15% water content, the fat/oil 7.69±1.24%, the levels of water-soluble substances 4.16±0.99%, levels of substances rawhide 42.47±6.39%, 0.99±0.03% levels of insoluble ash in the water, levels of tanning substances (tannins) bound 27.63±2.75% and 65.46% tanning degree, which all meet the quality standard ISO test 06-0994-1989 and SNI No.0253-2009.